Prices of Tradable and Nontradable Goods in the Demand for Total Imports - Goldstein, Morris; Khan, Mohsin S.; Officer, Lawrence H. (The Review of Economics and Statistics, 1980)
The following sections are included:INTRODUCTIONSPECIFICATION OF THE IMPORT EQUATIONRESULTSCONCLUSIONSREFERENCESAPPENDIX (This abstract was borrowed from another version of this item.)